2020
DOI: 10.1111/1756-185x.13930
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA GAS5 activates the AMPK pathway in peripheral blood mononuclear cells derived from rheumatoid arthritis patients

Abstract: Rheumatoid arthritis (RA) is an inflammatory disease characterized by destruction of synovial joints, 1 abnormal immune responses 2 and inflammatory manifestations, 3 which seriously affects human joints. 4 Although much progress has been made in the development of effective drugs for RA, the disease-associated disability rate is still high. Genetical studies have shown that rheumatoid factors 5 and a variety of inflammatory processes 6 play an important role in the mechanism of RA, albeit the etiology of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Our study showed that lnc‐GAS5 was positively associated with CRP, TNF‐α, and IL‐17 levels, while miR‐21 was negatively associated with CRP, TNF‐α, IL‐1β, IL‐6, and IL‐17 levels in CHD patients. The explanations might be as follows: (1) Lnc‐GAS5 intensified inflammation and inflammatory cytokines production via multiple pathways, such as the miR‑23a‑3p/TLR4, 10 miR‐223‐3p/NLRP3, 21 and AMP‐activated protein kinase pathways, 34 triggering increased CRP, TNF‐α, and IL‐17 levels; (2) miR‐21 downregulated TNF‐α, IL‐1β, IL‐6, and IL‐17 via the JNK signaling 23 and PI3K/AKT pathways, 24 leading to decreased pro‐inflammatory cytokines and CRP levels. Meanwhile, lnc‐GAS5 and miR‐21 presented high correlation coefficients with IL‐17, which could be explained by the regulation of lnc‐GAS5 and miR‐21 on T helper 17 balance and differentiation 35,36 …”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that lnc‐GAS5 was positively associated with CRP, TNF‐α, and IL‐17 levels, while miR‐21 was negatively associated with CRP, TNF‐α, IL‐1β, IL‐6, and IL‐17 levels in CHD patients. The explanations might be as follows: (1) Lnc‐GAS5 intensified inflammation and inflammatory cytokines production via multiple pathways, such as the miR‑23a‑3p/TLR4, 10 miR‐223‐3p/NLRP3, 21 and AMP‐activated protein kinase pathways, 34 triggering increased CRP, TNF‐α, and IL‐17 levels; (2) miR‐21 downregulated TNF‐α, IL‐1β, IL‐6, and IL‐17 via the JNK signaling 23 and PI3K/AKT pathways, 24 leading to decreased pro‐inflammatory cytokines and CRP levels. Meanwhile, lnc‐GAS5 and miR‐21 presented high correlation coefficients with IL‐17, which could be explained by the regulation of lnc‐GAS5 and miR‐21 on T helper 17 balance and differentiation 35,36 …”
Section: Discussionmentioning
confidence: 99%
“…It is also involved in RA pathogenesis by regulating IL-23R in RA patients to promote Th17 cell response ( 198 ). The expression levels of circ_0000396 and circ_0130438 in the PBMCs of RA patients ( n = 36) could serve as potential biomarkers for RA diagnosis, and they are significantly reduced in RA patients compared with HCs ( 199 ). Notably, circ_0008410 was significantly upregulated in the PBMCs of RA patients, while circ_0000175 was downregulated, and their expression levels were correlated with RA disease activity and severity.…”
Section: Candidate Rnas As Biomarkers For Ramentioning
confidence: 99%
“…However, some lncRNAs may relieve RA symptoms. For example, LncRNA GAS5 was downregulated in PBMC from RA, inhibiting IL-6 and IL-17 expression [ 63 ]. LncRNA 00197 regulated miR-150 to inactivate the TLR4/NF-κB pathway and reduce the activity of RA [ 64 ].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%